Incidence of cardiovascular diseases in a nationwide HIV/AIDS patient cohort in Taiwan from 2000 to 2014. Issue 16 (30th December 2018) - Lai, Yun-Ju; Chen, Yu-Yen; Huang, Hsin-Hui; Ko, Ming-Chung; Chen, Chu-Chieh; Yen, Yung-Feng
Abstract: The purpose of the study was to determine the incidence of cardiovascular disease (CVD) among people living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (PLWHA) in Taiwan. PLWHA were identified from the Taiwan Centers for Disease Control HIV Surveillance System between 2000 and 2014. To examine the effect of active antiretroviral therapy (HAART) on CVD incidence, incidence densities and standardised incidence rates (SIRs) of CVD were calculated after stratifying PLWHA by HAART. Of 26 272 PLWHA (mean age, 32.3 years) identified, 73.4% received HAART. Compared with general population, SIRs (95% confidence interval) were higher for incident coronary artery disease (1.11 (1.04–1.19)), percutaneous coronary intervention (1.32 (1.18–1.47)), coronary artery bypass surgery (1.47 (1.29–1.66)), sudden cardiac death (3.01 (2.39–3.73)), heart failure (1.50 (1.31–1.70)) and chronic kidney disease (1.95 (1.81–2.10)), but was lower for incident atrial fibrillation (0.53 (0.37–0.73)). Considering the effect of HAART on incident CVD, the SIRs for all-cause, ischaemic and haemorrhagic stroke were higher in PLWHA who did not receive HAART, but were lower in PLWHA who received HAART. PLWHA had higher risks of incident coronary artery disease, percutaneous coronary intervention, coronary artery bypass surgery, sudden cardiac death, heart failure and chronic kidney disease. HAART reduces risks of incident CVD in PLWHA.